PERBANDINGAN METODE DEMONSTRASI DAN METODE DISKUSI DALAM MENINGKATKAN PEMAHAMAN KONSEP TRIGONOMETRI PADA SISWA KELAS X SMASWASTA KAMPUS TELUK DALAM - Laia, Irman Imawan (Afore : Jurnal Pendidikan Matematika, 2024)
The purpose of this research is to determine the comparison of demonstration methods and discussion methods in increasing understanding of trigonometry concepts in Class X SMA Swasta Teluk Dalam. This research uses a type of quantitative research, namely experimental class 1 using the demonstration method and experimental class 2 using the discussion method. The population in experimental class 1 is class X-A of the SMA Swasta Teluk Dalam, totaling 30 students, while the population in experimental class 2 is class X-B of the SMA Swasta Teluk Dalam the totaling 28 students. Results of the research stated that in experimental class 1 by carrying out the pretest the average learning outcome was 58,28 and the posttest obtained an average learning outcome of 73,41. Meanwhile, in experimental class 2, the pretest obtained an average learning result of 57,85 and the posttest obtained an average learning result of 61,32. So, there is a comparison of the demonstration method with the discussion method. The conclusion of the research based on hypothesis test calculations is that tcount = 2.74 is greater than ttable = 2.004 with a significance of 5% because tcount > ttable then Ha is accepted and H0 is rejected, which means the research shows that there is a difference in understanding the concept of trigonometry between students taught using the demonstration method and students who are taught using the discussion method in class X of the SMA Swasta Teluk Dalam. Students taught using the demonstration method tend to have better understanding than students taught using the discussion method. It is hoped that every subject teacher applies the demonstration method to improve students' learning abilities and students' understanding of concepts in Trigonometry material as well as to serve as a guide or reference for every reader or researcher who wants to write their next thesis.